Assessment of Genetic Variation and Population Structure of Diverse Rice Genotypes Adapted to Lowland and Upland Ecologies in Africa Using SNPs - Ndjiondjop, Marie Noelle; Semagn, Kassa; Sow, Mounirou; Manneh, Baboucarr; Gouda, Arnaud C.; Kpeki, Sèdjro B.; Pegalepo, Esther; Wambugu, Peterson; Sié, Moussa; Warburton, Marilyn L. (Frontiers in Plant Science, 2018)
Using interspecific crosses involving Oryza glaberrima Steud. as donor and O. sativa L. as recurrent parents, rice breeders at the Africa Rice Center developed several ‘New Rice for Africa (NERICA)’ improved varieties. A smaller number of interspecific and intraspecific varieties have also been released as ‘Advanced Rice for Africa (ARICA)’. Here, we studied the genetic variation, relatedness, and population structure of 331 widely used rice genotypes in Africa using DArTseq-based single nucleotide polymorphisms (SNP). A sample of 1 aus, 11 ARICAs, 85 NERICAs, 62 japonica, and 172 indica genotypes were genotyped with 26,260 SNPs, of which 15,020 SNPs were polymorphic. Genetic distance between pairs of genotypes that belong to indica, japonica, ARICA and NERICA varied from 0.015 to 0.624, from 0.020 to 0.661, from 0.075 to 0.763, and from 0.014 to 0.644, respectively. The proportion of pairs of genotypes with genetic distance > 0.400 was the largest within NERICAs (35.1% of the pairs) followed by japonica (22.6%), ARICAs (18.2%), and indica (7.8%). We found one pair of japonica, 11 pairs of indica, and 35 pairs of NERICA genotypes differing by < 2% of the total scored alleles, which was due to 26 pairs of genotypes with identical pedigrees. Cluster analysis, principal component analysis, and the model-based population structure analysis all revealed two distinct groups corresponding to the lowland (primarily indica and lowland NERICAs) and upland (japonica and upland NERICAs) growing ecologies. Most of the interspecific lowland NERICAs formed a sub-group, likely caused by differences in the O. glaberrima genome as compared with the indica genotypes. Analysis of molecular variance revealed very great genetic differentiation (FST = 0.688) between the lowland and upland ecologies, and 31.2% of variation attributable to differences within cluster groups. About 8% (1,197 of 15,020) of the polymorphic SNPs were significantly (P < 0.05) different between the lowland and upland ecologies, and formed contrasting haplotypes that could clearly discriminate lowland from upland genotypes. This is the first study using high density markers that characterized NERICA and ARICA varieties in comparison with indica and japonica varieties widely used in Africa.